The Political Economy of Redistribution Policy - Luna Bellani; Heinrich Ursprung (Center for Economic Studies and ifo Institute (CESifo), 2016)
We review the literature on the public choice approach to explaining redistribution policies. The focus is on policies that are pursued with the sole reason to redistribute initial endowments. Moreover, we restrict ourselves to redistribution in democracies. In democratic settings, generic redistribution games lack equilibria. Structure-inducing rules that give rise to realistic redistribution patterns may concern the underlying economic model, political institutions, and firmly established preferences, beliefs, and attitudes of the voters. We present the respective lines of argument in turn and then present the related empirical evidence.
Keywords: D31; D72; I38; P16; 330; redistribution; political economy